La notion de « biens publics » au secours de la Politique Agricole Commune ? - François-Gaël Lataste; Aurélie Trouvé; Marielle Berriet-Solliec; Janet Dwyer (Développement Durable et Territoires, 2015)
For thirty years the Common Agricultural Policy (CAP) has undergone successive reforms, especially to justify agricultural public supports. The main argument to justify the CAP today is based on the economic concept of "public good". Using this concept helps to renew the initial European compromise of this policy based on the regulation of markets and farm income supports. Some British actors have played a vital role in the introduction of the term "public good" in community debates by defending a project of a radical reform of the CAP. This project , which in the case of England, was embodied in an alliance between environmentalists and landowners has finally not been retained in the reform of 2013, which maintains the importance of direct supports as principal tool.